2022
DOI: 10.1038/s41598-022-16610-8
|View full text |Cite
|
Sign up to set email alerts
|

SIRT4 functions as a tumor suppressor during prostate cancer by inducing apoptosis and inhibiting glutamine metabolism

Abstract: Localized in the mitochondria, SIRT4 is a nicotinamide adenine dinucleotide (NAD +) -dependent adenosine diphosphate (ADP) -ribosyltransferase and is one of the least characterized members of the sirtuin family. Although it is well known that it shows deacetylase activity for energy metabolism, little is understood about its function in tumorigenesis. Recent research suggests that SIRT4 may work as both a tumor suppressor gene and an oncogene. However, the clinical significance of SIRT4 in prostate cancer rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, the role of SIRT4 in bladder cancer has not been clari ed. Also in urological tumors, recently, we reported that SIRT4 is critical for prostate cancer [10]. Therefore, we would like to further explore the functional role of SIRT4 in bladder cancer.…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of SIRT4 in bladder cancer has not been clari ed. Also in urological tumors, recently, we reported that SIRT4 is critical for prostate cancer [10]. Therefore, we would like to further explore the functional role of SIRT4 in bladder cancer.…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of SIRT4 in bladder cancer has not been clarified. Additionally, in urological tumors, we recently reported that SIRT4 is critical for prostate cancer [ 10 ]. Therefore, we wanted to further explore the functional role of SIRT4 in bladder cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Breast cancer showed significant antitumor effects 47 ; in colorectal cancer studies, overexpression of SIRT4 was found to inhibit the metabolism of glutamine while also inhibiting the proliferation of rectal cancer cells through synergistic glucose inhibitors 48 ; glutamine transporter protein inhibitor V-9302 was able to selectively block triple-negative breast cancer (TNBC) cells' glutamine uptake and simultaneously enhance the immune response of T cells, suggesting that preferential inhibition of glutamine metabolism in tumor cells may represent a promising targeted therapy. 49 SIRT4 inhibits prostate cancer cell invasion and migration through inhibition of glutamine metabolism 22 ; in the context of radiation therapy of tumors, Mukha et al found that prostate cancer cells have a high glutamine requirement, and inhibition of GLS to target glutamine metabolism in prostate cells resulted in significant radiosensitization of cancer cells, 50,51 suggesting that inhibition of glutamine metabolism can be used as a prognostic biomarker and therapeutic target for radiosensitization of prostate cancer. SIRT4 inhibits B-cell lymphoma proliferation by inhibiting mitochondrial glutamine metabolism 52 ; in addition to this, SIRT4 inhibits B-cell lymphoma proliferation by inhibiting glutamine metabolism from suppressing the malignant biological behavior of thyroid cancer cells 53 ; In conclusion, these findings suggest the potential of SIRT4 for tumor-targeted therapeutic aspects, especially its potential to synergize with glutamine metabolism inhibitors for cancer treatment.…”
Section: Synergistic Glutamine Metabolismmentioning
confidence: 99%
“…In a recent prostate cancer study, overexpression of SIRT4 inhibited the proliferation, migration, and invasive ability of prostate cancer cells and promoted apoptosis of prostate cancer cells. In contrast, further studies indicated that SIRT4 could inhibit the proliferation, migration, and invasive ability of prostate cancer cells by inhibiting glutamine metabolism 22 . Current studies on SIRT4 in tumors prefer SIRT4 as a tumor suppressor, SIRT4 is a metabolism‐related factor with multiple enzymatic activities, and SIRT4 can inevitably have some effect on the malignant biological behavior of tumor cells by regulating the metabolism of tumor cells (Figure 3).…”
Section: Sirt4 and Cancermentioning
confidence: 99%